GREEN LOGISTICS STRATEGIES IN E-COMMERCE BALANCING SUSTAINABILITY AND COST EFFICIENCY - Pratiwi, Nurul Aziz (Penelitian dan Pengembangan Ilmu, 2025)
The rapid development of e-commerce in the last decade has brought significant environmental challenges, especially in the logistics sector which contributes greatly to global carbon emissions. This research aims to analyze green logistics strategies implemented by e-commerce companies and evaluate their effectiveness in balancing sustainability and cost efficiency. The method used is a Systematic Literature Review (SLR) with the PRISMA approach, which includes analysis of the latest literature regarding green logistics practices. The research results show that strategies such as sustainable packaging, carbon neutral shipping, route optimization, and collaboration with green suppliers can reduce environmental impact while increasing operational efficiency. However, challenges such as high initial costs, varying regulations, and consumer preferences for low prices are obstacles to implementing this strategy. This research provides recommendations for e-commerce companies to adopt more effective and sustainable green logistics practices.